Effect of Different Quenching Media on Microstructure, Hardness, and Wear Behavior of Steel Used in Petroleum Industries - Mohmmed, Jabbar Hussein; Al-hashimy, Zahid I. (Journal of Petroleum Research and Studies, 2018)
Medium carbon steel always used in most parts of the oil and gas industry, due to their cheap, simple manufacturing and easy deformation. However, as-rolled medium carbon steel usually does not meet the demands for many petroleum applications where high hardness and strength are needed; mainly because of their limitations in some mechanical features. Hence, many methods of thermal treatment techniques were adopted with a view to manipulate its structure and thus extend its scope of applications.This study focus on using a proper heat treatment to enhance medium carbon steel properties. Quenching and tempering treatments are usually the end of any manufacturing process to production of a machine component. However, the internal and residual stresses which generate during the heat treatments due to the non-uniform the quenched layer depth lead to distortion or cracked the machine component result in deteriorate the properties. Thus, the selection of optimum parameters of the quenching process is very important to ensure the achievement of the desired properties of the machine component. The main aim of this study is to get the optimal conditions for heat treatment which brought the best combination of mechanical properties of medium carbon steel without tempering treatment. Thus, in current study, an investigation of effects of polymer solution media on the quenching process was carried out with samples made of medium carbon steel. The samples were quenched in four different concentrations (0, 10, 15, 20) % of polymer (polyalkylene glycol) solution and set of quenched samples were tempered at 400 oC for 1h. The resulting as-quenched and tempered microstructures were compared and evaluated. Mechanical properties (hardness and wear rate) of the samples were determined using suitable standards. The results show that the quenched samples in polymer solution with 10% polyalkylene glycol were brought the best combination of mechanical properties as compared with other quenched and tempered samples.